CARING FOR OUR PEOPLE: INDIGENOUS RESPONSES TO COVID-19 ERA INFORMATIC COLONIALISM - Duarte, Marisa Elena; George, Alaina; Deschine-Parkhurst, Nicholet; Soto, Alexander (AoIR Selected Papers of Internet Research, 2021)
Based on qualitative and quantitative analyses, activist work and HCI approaches, these papers show how organizations formed partnerships to curate information resources, and deploy community Wi-Fi and Internet infrastructure across southwest US Indigenous communities during the most challenging months of the 2020 COVID-19 pandemic. For Native Americans this means ideating while navigating colonial inequality. Through an investigation of sociotechnical interdependencies across a broadband network cooperative, tribes, and university labs, an HCI team reflects on how relational stability sustains fragile Internet ecologies stretched to capacity by the needs of users deeply affected by COVID-19 in New Mexico and Arizona. Through an autoethnography of community-centered digital solutions for Navajo Nation, a member of the Nation considers how the role of K’é informs a system of infrastructural care in a nation struggling with high rates of infection and systemic lack of adequate infrastructure. Through an advocacy-oriented analysis of social media content, a Diné and Lakota social media scholar discerns the relationship between community enforcement of social distancing, the loss of interpersonal interaction, mutual aid, and the impact of public health memes for the Navajo Nation. Through radical librarianship practices, a Tohono O’odham librarian and artist counteracts the values of ‘information neutrality’ shaping whiteness-centering American librarianship by generating a community-curated solution to actionable information about COVID-19 for Indigenous communities. This panel models decolonial liberation rooted in responsiveness across mediated layers of Indigenous belonging. The authors express Indigenous interpretations of collective autonomy vis-a-vis strategic Internet assemblages, and particularly, how an Indigenous ethics of care intersects with the dream of an Internet for social good.